Bulbar involvement in patients with antiganglioside antibodies against NeuNAc(α2–3)Gal. Issue 6 (2nd September 2009) - Rojas-Garcia, Ricard; Gallardo, Eduard; De Luna, Noemi; Juarez, Candido; Martinez-Hernandez, Eugenia; Carvajal, Alejandra; Casasnovas, Carlos; Fages, Eva; Davila-González, Pablo; Illa, Isabel
Abstract : Background: Reactivity against terminal NeuNAc(α2–3)Gal, common to several gangliosides such as GD1a, GT1b and GM3, has rarely been reported. The authors recently described a patient with a clinical picture of acute relapsing sensory ataxic neuropathy and bulbar involvement in whom they demonstrated concomitant reactivity against NeuNAc(α2–3)Gal and disialosyl epitopes. The authors suggested a correlation between NeuNAc(α2–3)Gal reactivity and bulbar involvement. Aim: To determine the frequency of reactivity against terminal NeuNAc(α2–3)Gal in acute and chronic immune-mediated disorders, and its possible correlation with bulbar involvement. Methods: The authors retrospectively reviewed reactivity in the serum of more than 3000 consecutive patients with acute and chronic disorders in which antiganglioside antibodies were studied. The authors selected those patients who were simultaneously positive, by ELISA or thin-layer chromatography, for IgG or IgM antibodies anti-GM3, GD1a and GT1b, and reviewed their clinical features. Results: Reactivity against NeuNAc(α2–3)Gal, shared by GM3, GD1a and GT1b gangliosides, was detected in 10 patients: isolated in one patient, and concomitant with reactivity against other gangliosides in the remaining patients. Reactivity against NeuNAc(α2–3)Gal was frequently associated (8/10) with symptoms suggestive of bulbar involvement, such as dysphagia, dysarthria or dysphonia. Severe respiratory failure requiring mechanical ventilation was observed in four patients. Conclusions: Reactivity against the NeuNAc(α2–3)Gal epitope is rare and is generally found in association with reactivity against the disialosyl epitope. It can be detected in patients with acute or chronic disorders and could be a serological marker of clinical bulbar involvement and, to a lesser extent, associated with the development of severe respiratory failure.